Underwater searching system on unmanned surface vehicle - Liu, Jiaqi (2015)
RobotX is an international competition organized by Singapore and US, aiming to gather students with strong passion on surface robots. This year , the 1st competition is hosted by Singapore at Marina Bay Floating Area. One of the tasks is to build a search system to locate an underwater pinger (generating acoustic signal). [1st Award]